Analisis Mura’ah An-Nadzir : Penerapan Ilmu Badi’ dalam Ayat Al-Qur’an - Ismi Khairani; Masnida Wati Suryani; Harun Al-Rasyid (Jurnal Miftahul Ilmi: Jurnal Pendidikan Agama Islam, 2025)
Mura'ah an-Nadzir is a concept in badi' science which refers to the technique of combining harmonious and appropriate meanings in one expression without containing conflict. This technique plays an important role in creating rhetorical beauty and strengthening the delivery of the message. Through examples from the Qur'an, such as the combination of Allah's attributes in the sentence " وَهوَ السَّمِيعُ الْبَصِيرُ", it is explained how harmony between meanings can add depth and meaning to the message conveyed. Mura'ah an-Nadzir also has an aesthetic function, facilitating understanding, and emphasizing meaning in an educational context. In addition, this technique strengthens the moral message and evokes emotional interaction in the reader, making it an effective tool in spiritual communication. Thus, Mura'ah an-Nadzir not only functions as a linguistic technique, but also as a bridge to understanding and appreciating the beauty and depth of the Al-Qur'an as a holy book.